Steven Gamble, How Music Empowers: Listening to Modern Rap and Metal (Abingdon: Routledge, 2021). ISBN 9780367339555, 188 pp, £130 (hardback). (Journal of the Society for Musicology in Ireland, 2024)
A Review of Steven Gamble, How Music Empowers: Listening to Modern Rap and Metal (Abingdon: Routledge, 2021). ISBN 9780367339555, 188 pp, £130 (hardback).